The Role of Intellectual Capital on Financial Decision Making in Private Universities in Erbil City – Iraq - Ş. Gül Reís; Luqman M. Saeed; Kamal Mohammed Abdullah (Polytechnic Journal)
The purpose of the study is to examine the role of intellectual capital on financial decision making in private universities in Erbil. To achieve this purpose, the sample of the study collected from participating 115 managers at six private universities locating in Erbil city in Iraq. The dependent variable of the study is financial decision making. Independent variables are human capital, structural capital, and customer capital which are dimensions of intellectual capital according to Stewart model. In the methodology part of the study, the importance of working by focusing on some of the questions, posing the relationship between the independent and dependent variables, and the effectiveness have been determined. Accordingly, a conceptual model design of the study and then produce two main hypotheses to test. This has been subjected to numerous statistical tests. The study results; the most notable one is the existence of the highest rank of importance of human capital among intellectual capital components, while the customer and structural capitals come second and third, respectively. In addition, this result shows that the human, structural, and customer capitals affect financial decision making in Erbil private universities.